Colonic MALT Lymphoma Diagnosed 6 Months after Complete Remission of Gastric MALT Lymphoma - Kim, Seok Won; Kang, Sung Hoon; Kang, Sun Hyoung; Moon, Hee Seok; Sung, Jae Kyu; Jeong, Hyun Yong; Song, Gyu Sang (The Korean journal of medicine, 2016)
Mucosa-associated lymphoid tissue (MALT) lymphomas are a distinct group of malignant extranodal lymphoepithelial lesions. They were first described by Isaacson and Wright as lymphomas arising from MALT [1]. They can occur in almost any organ exposed to a persistent stimulus, such as chronic infection or an autoimmune condition [2]. The most common site is the stomach, and other gastrointestinal sites include the large and small bowel. Colonic MALT lymphoma is rare; here we report an extremely rare case of a primary colonic MALT lymphoma presenting 6 months after completion of radiation therapy for gastric MALT lymphoma. Most mucosa-associated lymphoid tissue (MALT) lymphomas are found in the gastrointestinal tract. The most common site is the stomach, whereas colon MALT lymphomas are rare. There are a few reports of simultaneously diagnosed stomach and colon MALT lymphomas. However, diagnosis of primary colonic MALT lymphoma after complete remission of gastric MALT lymphoma is extremely rare. Although the treatment protocol for gastric MALT lymphoma is well established, there is no consensus protocol for colonic MALT lymphoma owing to its rarity. Herein, we report a case of colonic MALT lymphoma incidentally diagnosed 6 months after completion of radiation therapy for gastric MALT lymphoma and treated via polypectomy, with no recurrence for 3 years. KCI Citation Count: 0